2013
DOI: 10.9767/bcrec.9.1.5529.53-59
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nanoporous Ni-Sn Alloy and Application for Chemoselective Hydrogenation of Furfural to Furfuryl Alcohol

Abstract: A very simple synthetic procedure was developed for the preparation of Ni-Sn alloy catalysts that were utilised for chemoselective hydrogenation of furfural, producing furfuryl alcohol almost exclusively. The mixture of nickel nanoparticles supported on aluminum hydroxide (R-Ni/AlOH) and a solution containing tin was treated under hydrothermal condition, producing the as prepared nickel-tin alloy supported on aluminum hydroxide (Ni-Sn/AlOH). H2 treatment at range of temperature of 673-873 K for 1.5 h to the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…The H2 uptake supported Ni-Sn alloy in this work was much lower than that of the Raney Ni or supported Ni on aluminium hydroxide, suggesting that the presence of second metal of Sn reduced significantly the accessibility of hydrogen on the surface of Ni metal. Consequently, the catalytic reaction may be effectively proceeded at high pressure of H2 as its have been reported previously [15][16][17][18][19],…”
Section: Catalyst Characterizationmentioning
confidence: 84%
See 1 more Smart Citation
“…The H2 uptake supported Ni-Sn alloy in this work was much lower than that of the Raney Ni or supported Ni on aluminium hydroxide, suggesting that the presence of second metal of Sn reduced significantly the accessibility of hydrogen on the surface of Ni metal. Consequently, the catalytic reaction may be effectively proceeded at high pressure of H2 as its have been reported previously [15][16][17][18][19],…”
Section: Catalyst Characterizationmentioning
confidence: 84%
“…NiCl2 or NiCl24H2O) produced from both bulk and supported Ni-Sn alloys [15] and, second, from Raney Ni-supported on aluminium hydroxide (R-Ni/AlOH), which produced a nickel-tin alloy supported on aluminium hydroxide (Ni-Sn(x)/AlOH; x = Ni/Sn molar ratio) [16]. We have also recently reported the catalytic performance of the Ni-Sn alloy during hydrogenation of biomass-derived levulinic acid in water to -valerolactone (GVL) [17]. Over bulk Ni-Sn alloy catalysts, a relatively high reaction temperature (150 o C, 40 bar H2, 6 h) was applied to achieve both a high conversion and GVL yield (99 %) [18].…”
Section: Introductionmentioning
confidence: 99%
“…We found that the catalyst that consisted of Ni-Sn alloy (as Ni3Sn2 species) dispersed on TiO2 allowed a remarkable reduction of the reaction temperature to 383 K. Our previous results have shown that the high conversion of FFald and the high selectivity of FFalc was achieved over Ni-Sn(1.5)/TiO2 catalyst that can be attributed to the relatively high dispersion of Ni-Sn alloy on TiO2 giving rise to active sites with a significantly higher catalytic activity [10]. The formation of Ni3Sn2 or Ni3Sn alloy phases after H2 treatment of Ni-Sn alloy catalysts supported on aluminium hydroxide are believed to play a key role in the enhancement of the chemoselectivity [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…We have reported a facile and efficient synthesis method of bimetallic Ni-Sn alloys both bulk and supported without organometallic tin precursor as starting materials via hydrothermal route from two types nickel metal precursor and its catalytic performances on [13,14] and selective hydrogenation of biomass-derived furfural into furfuryl alcohol with excellent activity and selectivity [15]. Firstly, from nickel chloride hexahydrate (NiCl2.6H2O) and tin chloride dihydrate (SnCl2·2H2O) to produce bulk and supported Ni-Sn alloy catalysts [13] and secondly, from Raney nickel supported on aluminium hydroxide (R-Ni/AlOH) and tin chloride dihydrate (SnCl2·2H2O) to obtain NiSn alloy supported on aluminium hydroxide (Ni-Sn/AlOH) [14,15] and applied for the chemoselective hydrogenation of α,β-unsaturated carbonyl compounds into unsaturated alcohol and selective hydrogenation of biomass-derived furfural into furfuryl alcohol with excellent activity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, from nickel chloride hexahydrate (NiCl2.6H2O) and tin chloride dihydrate (SnCl2·2H2O) to produce bulk and supported Ni-Sn alloy catalysts [13] and secondly, from Raney nickel supported on aluminium hydroxide (R-Ni/AlOH) and tin chloride dihydrate (SnCl2·2H2O) to obtain NiSn alloy supported on aluminium hydroxide (Ni-Sn/AlOH) [14,15] and applied for the chemoselective hydrogenation of α,β-unsaturated carbonyl compounds into unsaturated alcohol and selective hydrogenation of biomass-derived furfural into furfuryl alcohol with excellent activity and selectivity.…”
Section: Introductionmentioning
confidence: 99%